2017
DOI: 10.1038/onc.2017.270
|View full text |Cite|
|
Sign up to set email alerts
|

Toosendanin demonstrates promising antitumor efficacy in osteosarcoma by targeting STAT3

Abstract: Signal transducer and activator of transcription 3(STAT3) is an emerging target for cancer therapy. In this study, we identify Toosendanin (TSN) is an effective inhibitor of STAT3, leading to the impediment of various oncogenic processes in osteosarcoma. TSN selectively inactivates phospho-STAT3 (Tyr-705); subsequent molecular docking and in vitro SPR analysis uncover TSN directly binds to the SH2 domain of STAT3. Consequently, TSN blocks STAT3 dimerization and impairs the complex formation of STAT3 and epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 43 publications
4
90
0
Order By: Relevance
“…Our team previously reported that STAT3 is a critical regulator of osteosarcoma development and progression . The effect of RA on the JNK and STAT3 signaling pathways was assessed to investigate the molecular mechanism of the antitumor activity of RA using pharmacological inhibitors and shRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our team previously reported that STAT3 is a critical regulator of osteosarcoma development and progression . The effect of RA on the JNK and STAT3 signaling pathways was assessed to investigate the molecular mechanism of the antitumor activity of RA using pharmacological inhibitors and shRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the transient activation of STAT3 in normal cells, STAT3 remains abnormally active in tumors and promotes the induction and survival of cancer . Our previous results showed that selective inactivation of STAT3 blocks tumorigenesis in human osteosarcoma . Our most recent studies have shown that a natural compound, alternol, suppresses cell proliferation and migration and induces apoptosis and cell cycle arrest by modulating ROS‐dependent MAPK and STAT3 signaling pathways in human osteosarcoma cells .…”
Section: Introductionmentioning
confidence: 98%
“…The downstream signaling targets of c‐Met, including Akt, ERK and stat3, were also inhibited. The stat3 pathway was postulated to be important in OS formation because the selective inactivation of phospho‐stat3 blocks tumorigenesis in OS . In addition, Akt and ERK represent 2 of the most important intracellular pathways that drive tumor cell survival, transformation and proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…Three‐dimensional (3D) on‐top assay was performed as previously described . Briefly, 80 μL of Matrigel solution was added to a 48‐well plate, which was subsequently incubated at 37 °C to allowed the Matrigel to solidify.…”
Section: Methodsmentioning
confidence: 99%